Glycosylated coumarins, flavonoids, lignans and phenylpropanoids from Wikstroemia nutans and their biological activities - Wu, Meifang; Su, Xiangdong; Wu, Yichuang; Luo, Yuanjing; Guo, Ying; Xue, Yongbo (Beilstein Journal of Organic Chemistry, 2022)
Wikstroemia nutans Champ. ex Benth., a traditional herbal medicine collected at the Lingnan region of China, was chemically investigated. A new biscoumarin glucoside, wikstronutin (1), along with three known bis- and tricoumarin glucosides (2–4), two flavonoid glycosides (5–6), and eleven lignan glucosides (7–17) were isolated from the stems and roots of W. nutans. The new structure including its absolute configuration was elucidated based on a combination of 1D and 2D NMR, UV, IR, HRESIMS spectroscopic data, as well as chemical transformation. Compounds 1–17 were first isolated from the plant species W. nutans, while compounds 1–3, 8, and 11 were reported from the genus Wikstroemia for the first time. All co-isolates were evaluated for their in vitro inhibitory effects on nitric oxide (NO) production induced by lipopolysaccharide (LPS) in murine RAW264.7 macrophage cells. The antibacterial activity of the selected compounds was also tested. Our work enriches the structure diversity of the secondary metabolites from the genus Wikstroemia.
Keywords: coumarin glucosides; flavonoids; lignans; structure elucidation; Wikstroemia nutans

(untitled) - Lu, C.-L.; Zhu, L.; Piao, J.-H.; Jiang, J.-G. (Pharm. Biol. (Abingdon, U. K.), 2012)

(untitled) - Hua, P. (Ann. Bot. (Oxford, U. K.), 2007)

(untitled) - Li, Y.-M.; Zhu, L.; Jiang, J.-G.; Yang, L.; Wang, D.-Y. (Curr. Pharm. Biotechnol., 2009)

(untitled) - Moshiashvili, G.; Tabatadze, N.; Mshvildadze, V. (Fitoterapia, 2020)

(untitled) - Venugopala, K. N.; Rashmi, V.; Odhav, B. (BioMed Res. Int., 2013)

(untitled) - Al-Warhi, T.; Sabt, A.; Elkaeed, E. B.; Eldehna, W. M. (Bioorg. Chem., 2020)

(untitled) - Su, X.; Wu, Y.; Wu, M.; Lu, J.; Jia, S.; He, X.; Liu, S.; Zhou, Y.; Xing, H.; Xue, Y. (Molecules, 2021)

(untitled) - Jia, S.; Su, X.; Yan, W.; Wu, M.; Wu, Y.; Lu, J.; He, X.; Ding, X.; Xue, Y. (Front. Chem. (Lausanne, Switz.), 2021)

(untitled) - Liang, S.; Shen, Y.-H.; Tian, J.-M.; Wu, Z.-J.; Jin, H.-Z.; Zhang, W.-D.; Yan, S.-K. (Helv. Chim. Acta, 2009)

(untitled) - Liao, S.-G.; Zhang, B.-L.; Wu, Y.; Yue, J.-M. (Helv. Chim. Acta, 2005)

(untitled) - Wang, Q.; Jiang, Y.; Luo, C.; Wang, R.; Liu, S.; Huang, X.; Shao, M. (Bioorg. Med. Chem. Lett., 2018)

(untitled) - Baba, K.; Taniguti, M.; Yoneda, Y.; Kozawa, M. (Phytochemistry, 1990)

(untitled) - Zhong, X.-N.; Otsuka, H.; Ide, T.; Hirata, E.; Takushi, A.; Takeda, Y. (Phytochemistry, 1997)

(untitled) - Hara, H.; Ise, Y.; Morimoto, N.; Shimazawa, M.; Ichihashi, K.; Ohyama, M.; Iinuma, M. (Biosci., Biotechnol., Biochem., 2008)

(untitled) - Machida, K.; Sakamoto, S.; Kikuchi, M. (J. Nat. Med., 2009)

(untitled) - Iizuka, M.; Warashina, T.; Noro, T. (Chem. Pharm. Bull., 2001)

(untitled) - Salama, O.; Chaudhuri, R. K.; Sticher, O. (Phytochemistry, 1981)

(untitled) - Lee, D.-Y.; Song, M.-C.; Yoo, K.-H.; Bang, M.-H.; Chung, I.-S.; Kim, S.-H.; Kim, D.-K.; Kwon, B.-M.; Jeong, T.-S.; Park, M.-H.; Baek, N.-I. (Arch. Pharmacal Res., 2007)

(untitled) - Li, N.; Tan, N.; Zhou, J. (Acta Bot. Yunnanica, 2003)

(untitled) - Deyama, T.; Ikawa, T.; Nishibe, S. (Chem. Pharm. Bull., 1985)

(untitled) - Wang, C. Z.; Yu, D. Q. (Phytochemistry, 1998)

(untitled) - Kaneko, T.; Ohtani, K.; Kasai, R.; Yamasaki, K.; Nguyen, M. D. (Phytochemistry, 1998)

(untitled) - Çaliş, İ.; Saracoğlu, İ.; Başaran, A. A.; Sticher, O. (Phytochemistry, 1993)

(untitled) - Fukunaga, T.; Kajikawa, I.; Nishiya, K.; Takeya, K.; Itokawa, H. (Chem. Pharm. Bull., 1989)

(untitled) - Lee, I.-S.; Kim, Y. S.; Jung, S.-H.; Yu, S. Y.; Kim, J.-H.; Sun, H.; Kim, J. S. (Biosci., Biotechnol., Biochem., 2015)

(untitled) - Dembitsky, V. M. (Lipids, 2005)

(untitled) - Al-Majedy, Y. K.; Kadhum, A. A. H.; Al-Amiery, A. A.; Mohamad, A. B. (Syst. Rev. Pharm., 2017)

(untitled) - Wu, Y.; Xie, S.-s.; Hu, Z.-x.; Wu, Z.-d.; Guo, Y.; Zhang, J.-w.; Wang, J.-p.; Xue, Y.-b.; Zhang, Y.-h. (Chin. Herb. Med., 2017)

(untitled) - Zhang, N.; Shi, Z.; Guo, Y.; Xie, S.; Qiao, Y.; Li, X.-N.; Xue, Y.; Luo, Z.; Zhu, H.; Chen, C.; Hu, L.; Zhang, Y. (Org. Chem. Front., 2019)

(untitled) - Tanaka, T.; Nakashima, T.; Ueda, T.; Tomii, K.; Kouno, I. (Chem. Pharm. Bull., 2007)